Handbook of research on nonprofit economics and management - Seaman, Bruce A. (Bruce Alan), 1949-; Young, Dennis R., 1943- (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2010)
Nonprofit organizations are arguably the fastest growing and most dynamic part of modern market economies in democratic countries. This title explores the frontiers of knowledge at the intersection of economics and the management of nonprofit organizations. This book reviews the role, structure and behavior of private, nonprofit organizations as economic entities and their participation in markets and systems of public service delivery.
Introduction: the frontiers of economics and nonprofit management research / Bruce A. Seaman and Dennis R. Young -- Income diversification / Cyril F. Chang and Howard P. Tuckman -- Revenue interactions: crowding out, crowding in, or either? / Daniel Tinkelman -- Distribution policies of private foundations / Richard Sansing -- Capital formation / Robert J. Yetman -- Asset composition / Woods Bowman -- Collaboration versus competition in the third sector / Renée A. Irvin -- Markets with competition between for-profit and nonprofit firms / Eleanor Brown -- Nonprofit wages: theory and evidence / Anne E. Preston and Daniel W. Sacks -- Modeling nonprofit behavior / Patricia Hughes and William Luksetich -- Pricing strategies / Bruce A. Seaman -- Nonprofits and the value of risk management / Martin F. Grace -- Contracting out / Salvatore Alaimo -- Product diversification and social enterprise / Sharon M. Oster -- Internal organization and governance / Vladislav Valentinov -- Franchises and federations: the economics of multi-site nonprofit organizations / Dennis R. Young and Lewis Faulk -- The valuation of volunteer labor / Laura Leete -- Assessing nonprofit performance / Joseph J. Cordes and Katherine Coventry -- Social accounting for value creation in nonprofits / Laurie Mook and Femida Handy -- Certification and self-regulation of nonprofits, and the institutional choice between them / Andreas Ortmann and Jan Myslivecek -- Federal tax policy / Michael Rushton -- The property tax exemption for nonprofits / David L. Sjoquist and Rayna Stoycheva -- Government funding policies / Stefan Toepler.
Originally published: 2010.
&#x000A
Includes bibliographical references and index.
oif 22/05/13
Loan
Keywords: Nonprofit organizations -- Management; Nonprofit organizations -- Economic aspects; Nonprofit organizations -- Handbooks, manuals, etc; Nonprofit organizations -- Finance; Management